Calculus workbook for dummies - Ryan, Mark, 1955- (Hoboken, NJ : John Wiley & Sons, Inc., 2018)
"Calculus is tough--no doubt about it. But now you can leave your fear at the door! Inside, you'll find problems involving trigonometric, logarithmic, and exponential functions, as well as limits, continuity, differentiation, integration, and infinite series. Plus, you'll get more than 500 practice problems inside and online, with detailed solutions that will help you master the math that is critical for scoring your highest in calculus"--
"With online practice"--Title page.
Includes index.
Keywords: Calculus; Calculus -- Problems, exercises, etc; MATHEMATICS / Calculus; MATHEMATICS / Mathematical Analysis; Calculus; Analysis; Differentialrechnung; Problems and exercises